Diagnosis and treatment of liver serosis (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Chronic liver disease (CLD) is an epidemic that has not been taken into account. Early death is plentiful and liver disease in the country, along with heart and respiratory disease, is among the first three in unfair health care. Fifty percent of patients with CLD are diagnosed with cirrhosis for the first time after emergency medical treatment, leading to poor patient outcomes. Traditional care models are based on secondary care when need is at the society level. Screening patients for the presence of the disease based on risk factors at population level in society allows them to determine its presence early in the presence of potential reactivity